2020
DOI: 10.1155/2020/2123652
|View full text |Cite
|
Sign up to set email alerts
|

Latrine Ownership and Its Determinants in Rural Villages of Tigray, Northern Ethiopia: Community-Based Cross-Sectional Study

Abstract: Background. Open defecation was largely a rural phenomenon most widely attributed to poor latrine ownership at community level. We aimed at examining latrine ownership and its determinants in rural villages of the Tigray region, Northern Ethiopia. Methods. Community-based cross-sectional study was conducted from June to July 2018. A total of 756 randomly selected households were involved in the study. The multistage cluster sampling technique was used to select study households. Data were checked, coded, and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
(44 reference statements)
1
4
0
Order By: Relevance
“…Similarly , households whose toilets were placed in their own yard were 1.2 times more likely to access appropriate sanitation services than households whose toilets were placed elsewhere. This finding is supported by studies done in northern [ 42 ], and northwest Ethiopia [ 54 ]. This might be because households need to access and utilize functional toilet facilities within their own privacy, security, and comfort [ 54 , 55 ].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Similarly , households whose toilets were placed in their own yard were 1.2 times more likely to access appropriate sanitation services than households whose toilets were placed elsewhere. This finding is supported by studies done in northern [ 42 ], and northwest Ethiopia [ 54 ]. This might be because households need to access and utilize functional toilet facilities within their own privacy, security, and comfort [ 54 , 55 ].…”
Section: Discussionsupporting
confidence: 82%
“…The interpolation result indicated that households in the Northern Amhara, Western Gambela, Tigray, Afar, Somali, and Harari regions, as well as in Addis Ababa and Dire Dawa cities, would be less vulnerable to poor sanitation service access. However, SNNPR, Binishangul Gumez, Oroima, and Southern Amhara regions would be more vulnerable to poor sanitation service access The vulnerability of households to poor sanitation service access in Ethiopia might be due to a lack of information [ 11 ], low latrine ownership [ 42 ], poor latrine conditions, structure, and design [ 43 ], and a lack of total sanitation and hygiene intervention led by the community [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Open defecation is mainly a rural phenomenon ascribed to poor latrine ownership at the community and household levels [ 38 ]. The results from the review showed that increased latrine ownership by individual households contributes to improved WaSH practices in a community [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Education and household size were among the determinants of open defecation, which is related to the lack of latrine ownership in the Wa Municipality of Ghana [ 22 ]. Ajemu et al [ 29 ] reported that promotion of Health Extension Workers, possession of private houses, and occupational status were more likely to be associated with latrine construction among some rural villages of Tigray region, northern Ethiopia.…”
Section: Discussionmentioning
confidence: 99%